Social entrepreneurship : from issue to viable plan - Barreiro, Terri D. (2013 digital library., 2013)
This book provides a guided deep dive into the early stages of venture development of social entrepreneurship. It introduces concepts that provide important insights necessary for social venture success. It introduces a set of entrepreneurial tools designed for the unique set of challenges faced in selecting and designing social entrepreneurial ventures. With this book as a guide, the reader can develop a feasible venture concept and communicate it effectively.